Association of genetic and psychological factors with persistent pain after cosmetic thoracic surgery - Dimova, Violeta; Loetsch, Joern; Hühne, Kathrin; Winterpacht, Andreas; Heesen, Michael; Parthum, Andreas; Weber, Peter G.; Carbon, Roman; Grießinger, Norbert; Sittl, Reinhard; Lautenbacher, Stefan (Journal of Pain Research, 2015)
The genetic control of pain has been repeatedly demonstrated in human association studies. In the present study, we assessed the relative contribution of 16 single nucleotide polymorphisms in pain-related genes, such as cathechol-O-methyl transferase gene (COMT), fatty acid amino hydrolase gene (FAAH), transient receptor potential cation channel, subfamily V, member 1 gene (TRPV1), and ?-opioid receptor gene (OPRD1), for postsurgical pain chronification. Ninety preoperatively pain-free male patients were assigned to good or poor outcome groups according to their intensity or disability score assessed at 1 week, 3 months, 6 months, and 1 year after funnel chest correction. The genetic effects were compared with those of two psychological predictors, the attentional bias toward positive words (dot-probe task) and the self-reported pain vigilance (Pain Vigilance and Awareness Questionnaire [PVAQ]), which were already shown to be the best predictors for pain intensity and disability at 6 months after surgery in the same sample, respectively. Cox regression analyses revealed no significant effects of any of the genetic predictors up to the end point of survival time at 1 year after surgery. Adding the genetics to the prediction by the attentional bias to positive words for pain intensity and the PVAQ for pain disability, again no significant additional explanation could be gained by the genetic predictors. In contrast, the preoperative PVAQ score was also, in the present enlarged sample, a meaningful predictor for lasting pain disability after surgery. Effect size measures suggested some genetic variables, for example, the polymorphism rs1800587G>A in the interleukin 1 alpha gene (IL1A) and the COMT haplotype rs4646312T>C/rs165722T>C/rs6269A>G/rs4633T>C/rs4818C>G/rs4680A>G, as possible relevant modulators of long-term postsurgical pain outcome. A comparison between pathophysiologically different predictor groups appears to be helpful in identifying clinically relevant predictors of chronic pain.
EVALuna2:9288

Consultation with a specialized pain clinic reduces pain after oral and maxillofacial surgery - Dietrich, Eva-Maria; Grießinger, Norbert; Neukam, Friedrich Wilhelm; Schlittenbauer, Tilo (Journal of Cranio-Maxillofacial Surgery, 2016)
Postoperative pain management is important for improved patient care. Our primary objective was to investigate the effect of analgesic treatment adaptation by the pain clinic on postoperative pain relief at an oral and maxillofacial surgery department. Additionally, we aimed to present patients' pain characteristics and the administered analgesic treatment.A total of 128 patients treated at our clinic in the period 2012-2015 who required analgesic treatment adaptation by our pain clinic were included. They were further divided into 10 groups: tumor, temporomandibular joint disorder, tooth extraction, osteomyelitis, bisphosphonate-related osteonecrosis of the jaw, submandibular abscess, orthognathic surgery, cyst, sinusitis, and fracture. Pain characteristics evaluated were intensity on a numerical rating scale (NRS) before and after intervention of the pain clinic, quality, genesis, and type.Post treatment pain intensity values at rest 1.8 (SD: 1.4) and on exercise (walking and physical therapy) 4 (SD: 2) were statistically significant better compared to pretreatment values (4.2, SD: 2.5, and 6.8 SD: 2, respectively). The highest pain intensities were reported after tooth extractions, orthognathic surgery, cystectomies, and fracture reposition. Pain was mainly continuous and related to a combination of a somatic and a neuropathic pathophysiological mechanism.Intervention by a specialized pain clinic leads to reduction of postoperative pain.
EVALuna2:16744

Emergent biomarker derived from next-generation sequencing to identify pain patients requiring uncommonly high opioid doses - Kringel, D.; Ultsch, A.; Zimmermann, M.; Jansen, J. P.; Ilias, W.; Freynhagen, R.; Grießinger, Norbert; Kopf, A.; Stein, C.; Doehring, A.; Resch, E.; Lötsch, J. (Pharmacogenomics Journal, 2016)
Next-generation sequencing (NGS) provides unrestricted access to the genome, but it produces 'big data' exceeding in amount and complexity the classical analytical approaches. We introduce a bioinformatics-based classifying biomarker that uses emergent properties in genetics to separate pain patients requiring extremely high opioid doses from controls. Following precisely calculated selection of the 34 most informative markers in the OPRM1, OPRK1, OPRD1 and SIGMAR1 genes, pattern of genotypes belonging to either patient group could be derived using a k-nearest neighbor (kNN) classifier that provided a diagnostic accuracy of 80.6±4%. This outperformed alternative classifiers such as reportedly functional opioid receptor gene variants or complex biomarkers obtained via multiple regression or decision tree analysis. The accumulation of several genetic variants with only minor functional influences may result in a qualitative consequence affecting complex phenotypes, pointing at emergent properties in genetics.The Pharmacogenomics Journal advance online publication, 3 May 2016; doi:10.1038/tpj.2016.28.
EVALuna2:16735

Erratum to: Opioids for noncancer pain in the elderly - Schuler, M.; Grießinger, Norbert (Schmerz, 2015)
EVALuna2:16689

Prediction of persistent post-operative pain: Pain-specific psychological variables compared with acute post-operative pain and general psychological variables - Horn-Hofmann, C.; Scheel, J.; Dimova, V.; Parthum, A.; Carbon, R.; Grießinger, Norbert; Sittl, R.; Lautenbacher, S. (European Journal of Pain, 2018)
BACKGROUND: Psychological variables and acute post-operative pain are of proven relevance for the prediction of persistent post-operative pain. We aimed at investigating whether pain-specific psychological variables like pain catastrophizing add to the predictive power of acute pain and more general psychological variables like depression. METHODS: In all, 104 young male patients undergoing thoracic surgery for pectus excavatum correction were studied on the pre-operative day (T0) and 1 week (T1) and 3 months (T2) after surgery. They provided self-report ratings (pain-related: Pain Catastrophizing Scale, Pain Anxiety Symptoms Scale = PASS, Pain Vigilance and Awareness Questionnaire = PVAQ; general psychological: Screening for Somatoform Symptoms, State-Anxiety Inventory-X1, Center for Epidemiologic Studies Depression Scale = CES-D). Additional predictors (T1) as well as criterion variables (T2) were pain intensity (Numerical Rating Scale) and pain disability (Pain Disability Index). RESULTS: Three months after surgery, 25% of the patients still reported clinically relevant pain (pain intensity ≥3) and over 50% still reported pain-related disability. Acute post-operative pain as well as general psychological variables did not allow for a significant prediction of persistent post-operative pain; in contrast, pain-related psychological variables did. The best single predictors were PASS for pain intensity and PVAQ for pain disability. CONCLUSIONS: Pain-related psychological variables derived from the fear-avoidance model contributed significantly to the prediction of persistent post-operative pain. The best possible compilation of these measures requires further research. More general psychological variables may become relevant predictors later in the medical history. SIGNIFICANCE: Our results suggest that pain-specific psychological variables such as pain anxiety and pain hypervigilance add significantly to the prediction of persistent post-operative pain and might even outperform established predictors such as acute pain and general psychological variables. Clinicians might benefit from the development of time-economic screening tools based on these variables.
EVALuna2:36086

Psychological Predictors of Acute Postoperative Pain after Hysterectomy for Benign Causes - Scheel, Jennifer; Sittl, Reinhard; Grießinger, Norbert; Strupf, Marion; Parthum, Andreas; Dimova, Violeta; Horn-Hofmann, Claudia; Thiel, Falk; Beckmann, Matthias; Lautenbacher, Stefan (Clinical Journal of Pain, 2016)
Psychological parameters have been shown to contribute significantly to the development of acute postoperative pain (APOP). For the prediction of APOP in chest malformation patients and cancer patients, we found pain-specific psychological predictors to be of higher relevance than general psychological predictors. The current study aims to further substantiate these findings.In a sample of 73 middle-aged hysterectomy patients, three predictor sets were assessed 1 day before surgery: attentional biases (towards pain-related, social threat, and positive words in a dot-probe task), pain-related emotions and cognitions (pain anxiety, pain catastrophizing, and pain hypervigilance), and affective state variables (depression and somatization). APOP intensity rated 2-3 days after surgery and analgesic consumption during the first 48 postoperative hours were used as outcome measures.APOP intensity ratings were significantly explained by their best single predictors in a multiple regression analysis: social threat words of the dot-probe task, pain anxiety, and somatization (14.7% of explained variance). When comparing standardized beta coefficients, pain-specific psychological predictors appeared to be of higher explanatory relevance than general psychological predictors. In contrast, analgesic consumption could not be significantly predicted by the psychological variables.Hysterectomy patients at risk for high APOP intensity could be characterized by the psychological variables used, whereas their predictive value for analgesic consumption was limited. The high predictive potency of pain-specific psychological variables should be considered for further improvement of pain management and prevention, because pain-specific variables like pain anxiety can be the target of focal psychological interventions when preparing for surgery.
EVALuna2:16734

Psychological prophylaxis training for coping with postoperative pain. Long-term effects - Scheel, J.; Parthum, A.; Dimova, V.; Horn-Hoffmann, C.; Meinfelder, F.; Carbon, R.; Grießinger, Norbert; Sittl, R.; Lautenbacher, S. (Schmerz, 2014)
The present study was performed to investigate the effect of multidimensional psychological prophylaxis training focusing on coping with cognitive-emotional pain on recovery within the first 12 months after surgery. The training included the following three components: (1) education about pain, analgesia and psychological aspects of coping with pain, (2) training for coping with pain and (3) body-centered relaxation.In the study 48 young male patients (surgical correction of a chest malformation) were assessed 1 day before surgery, at discharge and 3, 6 and 12 months postoperatively concerning postoperative pain intensity and pain disability as well as pain anxiety, pain catastrophizing and pain hypervigilance. Additionally, 24 of these patients received training on cognitive-emotional coping with pain 1 day before surgery and 1-3 days after surgery (each session 1 h).The proportion of patients with clinically relevant improvement was significantly higher in the training group compared to the control group. This was the case for acute pain intensity (approximately 1 week after surgery), pain disability 3 months later and pain anxiety 12 months after surgery.The resurgence of pain anxiety after 12 months could only be found in the control group and could be due to the upcoming surgical removal of the transsternal metal implant. The prophylaxis training can therefore be seen as a protective factor for long-term management of surgery-related consequences and future pain experiences.
EVALuna2:15688